2008
DOI: 10.1021/jo8010254
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of Allylic Coupling Reactions: A Hammett Analysis of the Coupling of Aryl Silicate Derivatives

Abstract: Hammett analysis of the palladium-catalyzed allyl-aryl coupling reaction has demonstrated that the rate of the coupling reaction is enhanced by electron-withdrawing groups on the aryl siloxane. The positive slope of the Hammett plot indicated involvement of a charged transition state in which negative charge on the aryl ring is stabilized inductively. This result is consistent with either transmetalation or reductive elimination being the rate-determining step in the coupling process. Furthermore, the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 113 publications
1
17
0
1
Order By: Relevance
“…Portanto, grupos eletrorretiradores como R' aumentarão a velocidade da transmetalação quando o acoplamento ocorrer com bromoarenos e isso corrobora a observação feita por DeShong e Shukla. 16 Contudo, tais suposições carecem de maiores investigações para total comprovação.…”
Section: Resultsunclassified
“…Portanto, grupos eletrorretiradores como R' aumentarão a velocidade da transmetalação quando o acoplamento ocorrer com bromoarenos e isso corrobora a observação feita por DeShong e Shukla. 16 Contudo, tais suposições carecem de maiores investigações para total comprovação.…”
Section: Resultsunclassified
“…DeSong and co-workers performed a Hammett analysis of the Pd-catalyzed coupling between ethyl 2-cyclohexenylcarbonate (396) and para-substituted phenyl siloxanes. [116] A linear Hammett correlation (log(k rel ) versus s) was obtained from a series of pair-wise competitive experiments in which a mixture of triethoxy(phenyl)silane (397) and 398 (R = OMe, Me, Cl, CO 2 Et, 1.42 mmol of each) was reacted with 396 (0.712 mmol) as the coupling partner and [Pd(dba) 3 ] (0.0712 mmol) as the pre-catalyst in the presence of TBAF (2.85 mmol) (Scheme 80). The competitive experiments demonstrated that phenyl siloxanes carrying an electron-withdrawing para-substituent were the most reactive.…”
Section: Allyl-aryl Couplingsmentioning
confidence: 99%
“…For example, the electronic influence of organic reagents on transmetallation is not well understood and contradictory conclusions have been reported. [19][20][21][22] Organoboron compounds are one of Page 2 of 18 CCS Chemistry 3 the most diverse classes of easily obtained reagents, 23 and provide access to a raft of valuable indispensable transformations such as Suzuki-Miyaura coupling, Chan-Evans-Lam coupling, 24 oxidative coupling 25 and so on. 26 They undergo facile transmetallation with various transition metals in the presence of base.…”
Section: Introductionmentioning
confidence: 99%